Observation of β-delayed two-proton emission in the decay of 22Si - X.X. Xu; C.J. Lin; L.J. Sun; J.S. Wang; Y.H. Lam; J. Lee; D.Q. Fang; Z.H. Li; N.A. Smirnova; C.X. Yuan; L. Yang; Y.T. Wang; et al. (Physics Letters B, 2017)
The decay of the lightest nucleus with Tz=−3, 22Si, was studied by a silicon array. A charged-particle group at 5600 (70) keV in the decay-energy spectrum was identified experimentally as β-delayed two-proton emission from the isobaric analog state (IAS) of 22Al. Experimental results of the IAS fed by a superallowed Fermi transition were compared with our large-scale shell-model calculations. The ground-state mass of 22Si was obtained indirectly in the experiment for the first time. Two-proton separation energy for 22Si is deduced to be −108 (125) keV, which indicates that it is a very marginal candidate for two-proton ground-state emission.